Analysing Window Flowing Control Mechanism of Packet Switching Networks Based on Stochastic Petri Nets - Si Yujuan Lang Liuqi Zhou Li Dai Yisong (Tongxin xuebao)
In this paper,by using queuing networks and stochastic Petri nets technique,window flow control mechanism in network layer of packet switching net can be described and analysed in detailed and then their SPN models are established,SPN reachability graph of stochatic petri nets and state equation are put forward.A new way is given for property analysis and evaluation of communication networks.